2016
DOI: 10.1002/app.44173
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐swelling superabsorbent polymers with polymerizable macromolecular surfactant as crosslinker

Abstract: Fast‐swelling superabsorbent polymers (SAPs) have been prepared by micellar cross‐linking copolymerization of acrylic acid and acrylamide using polymerizable macromolecular surfactants (PMSs) as multifunctional crosslinkers, with a foaming technique. Sodium bicarbonate (NaHCO3)/acetone and Pluronic F127 were used as foam (or porosity) generators and stabilizer, respectively. It has been found that the PMSs with different polyethylene glycol (PEG) chain length have little effect on the swelling rate of the SAPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, viscosity was decreased for other NaPA by increasing testing time and the viscosity slightly increased. Increasing cross-linker content leads to reduced swelling (Figure 6) and the movement of polymer networks is restricted (Chen and Huang, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, viscosity was decreased for other NaPA by increasing testing time and the viscosity slightly increased. Increasing cross-linker content leads to reduced swelling (Figure 6) and the movement of polymer networks is restricted (Chen and Huang, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The specific surface area could be enhanced by the generation of a porous structure in SAP to absorb a large amount of water in a short amount of time [17]. There are various methods to prepare the porous structure of SAPs, such as phase inversion [18], freeze-drying and hydration, water-soluble porogens, and foaming [19]. Kabiri et al [20] utilized acetone and sodium bicarbonate as the porogens to prepare a high-porosity structure by optimizing reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the fast Q t s of SAPs mainly resulted from the faster diffusion of water into the polymeric network through the capillary effect of the porous microstructure . In recent years, SAPs with porous microstructures were obtained through the phase‐separation technique, freeze‐drying technology, and the introduction of foaming agents and water‐soluble porogens in an aqueous solution polymerization . Ma et al .…”
Section: Introductionmentioning
confidence: 99%
“…reported ecofriendly, crosslinked guar gum‐ g ‐poly(acrylate) porous superabsorbent hydrogels with the addition of foam stabilizer and water‐soluble porogens exhibited higher swelling ratios in various environments than the corresponding nonporous superabsorbent hydrogel. The SAPs prepared through a physical or chemical foaming system presented high water‐absorption abilities and fast Q t s, but the methods mainly yielded SAPs with broad macropore size distributions with a mixture of open and closed pores . Recently, it was reported that SAPs obtained with an interconnected open cellular structure with an anionic surfactant as a pore‐forming micelle template presented excellent Q t s .…”
Section: Introductionmentioning
confidence: 99%